Natural history of lung function in spinal muscular atrophy - Camiel A. Wijngaarde (Orphanet Journal of Rare Diseases, 2020)
Abstract Background Respiratory muscle weakness is an important feature of spinal muscular atrophy (SMA). Progressive lung function decline is the most important cause of mortality and morbidity in patients. The natural history of lung function in SMA has, however, not been studied in much detail. Results We analysed 2098 measurements of lung function from 170 treatment-naïve patients with SMA types 1c–4, aged 4–74 years. All patients are participating in an ongoing population-based prevalence cohort study. We measured Forced Expiratory Volume in 1 s (FEV1), Forced Vital Capacity (FVC), and Vital Capacity (VC). Longitudinal patterns of lung function were analysed using linear mixed-effects and non-linear models. Additionally, we also assessed postural effects on results of FEV1 and FVC tests. In early-onset SMA types (1c–3a), we observed a progressive decline of lung function at younger ages with relative stabilisation during adulthood. Estimated baseline values were significantly lower in more severely affected patients: %FEV1 ranged from 42% in SMA type 1c to 100% in type 3b, %FVC 50 to 109%, and %VC 44 to 96%. Average annual decline rates also differed significantly between SMA types, ranging from − 0.1% to − 1.4% for FEV1, − 0.2% to − 1.4% for FVC, and + 0.2% to − 1.7% for VC. In contrast to SMA types 1c–3a, we found normal values for all outcomes in later-onset SMA types 3b and 4 throughout life, although with some exceptions and based on limited available data. Finally, we found no important differences in FVC or FEV1 values measured in either sitting or supine position. Conclusions Our data illustrate the longitudinal course of lung function in patients with SMA, which is characterised by a progressive decline in childhood and stabilisation in early adulthood. The data do not support an additional benefit of measuring FEV1 or FVC in both sitting and supine position. These data may serve as a reference to assess longer-term outcomes in clinical trials.